2020
DOI: 10.1101/2020.06.29.178889
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Discovery of Synergistic and Antagonistic Drug Combinations against SARS-CoV-2 In Vitro

Abstract: AbstractCOVID-19 is undoubtedly the most impactful viral disease of the current century, afflicting millions worldwide. As yet, there is not an approved vaccine, as well as limited options from existing drugs for treating this disease. We hypothesized that combining drugs with independent mechanisms of action could result in synergy against SARS-CoV-2. Using in silico approaches, we prioritized 73 combinations of 32 drugs with potential activity again… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 85 publications
1
37
0
Order By: Relevance
“…It was also reported that remdesivir and HCQ exhibited a strong antagonism (28). Here, we showed that a combination of the replication inhibitor, remdesivir with the autophagy inhibitor, GNS561 demonstrated strong synergy in vitro, supporting future clinical evaluation of such combination regimens.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…It was also reported that remdesivir and HCQ exhibited a strong antagonism (28). Here, we showed that a combination of the replication inhibitor, remdesivir with the autophagy inhibitor, GNS561 demonstrated strong synergy in vitro, supporting future clinical evaluation of such combination regimens.…”
Section: Discussionsupporting
confidence: 70%
“…Thus, there is some interest in using drug combinations against SARS-CoV-2. Interestingly, it was recently reported that nitazoxanide in combination with amodiaquine, umifenovir or remdesivir presented a significant synergy against SARS-CoV-2 (28).…”
Section: Discussionmentioning
confidence: 99%
“…The study reported high synergy of nitazoxanide with three antivirals remdesivir, amodiaquine and umifenovir. The study also reports that the combination of remdesivir and hydroxychloroquine demonstrated strong antagonism ( Bobrowski et al, 2020 ). The combination use of nitazoxanide with macrolide antibiotic azithromycin ( Kelleni, 2020 ) and antimalarial drug hydroxychloroquine has been proposed ( Padmanabhan, 2020 ).…”
Section: Clinical Trials Of Nitazoxanide Against Covid-19mentioning
confidence: 93%
“…A significant finding is the ability of nitazoxanide to promote balance between pro-inflammatory and anti-inflammatory responses in humans, which could play a crucial role in COVID-19 by curbing the hyperinflammatory cytokine storm ( Jasenosky et al, 2019 ; Martins-Filho et al, 2020 ; Rossignol, 2016 ; Shakya et al, 2018a ). Repurposing nitazoxanide against COVID-19 has been suggested in many reports ( Alonso and Farina, 2020 ; Arshad et al, 2020 ; Bobrowski et al, 2020 ; Chibber et al, 2020 ; Mahmoud et al, 2020 ; Martins-Filho et al, 2020 ; Padmanabhan, 2020 ; Padmanabhan and Padmanabhan, 2020 ; Pepperrell et al, 2020 ; Rajoli et al, 2020 ). The approval of a number of clinical trials with nitazoxanide further substantiates this hypothesis ( https://clinicaltrials.gov/ ) (Nitazoxanide clinical trials, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…As described in Ellinger et al, 36 In addition, recently published data from the work of Bobrowski et al 37 , were mapped to the COVID-19 supergraph and compared to the results of the combinatorial treatment experiments performed here.…”
Section: Drug Combinations Assessment With Anti-cytopathic Effect Meamentioning
confidence: 99%